Effect of Dietary Omega-3 Polyunsaturated Fatty Acids on Heart Rate and Heart Rate Variability in Animals Susceptible or Resistant to Ventricular Fibrillation - Billman, George E. (Frontiers in Physiology, 2012)
The consumption of omega-3 polyunsaturated fatty acids (n-3 PUFAs) has been reported to reduce cardiac mortality following myocardial infarction as well as to decrease resting heart rate (HR) and increase heart rate variability (HRV). However, it has not been established whether n-3 PUFAs exhibit the same actions on HR and HRV in individuals known to be either susceptible or resistant to ventricular fibrillation (VF). Therefore, HR and HRV (high frequency and total R-R interval variability) were evaluated before and 3 months after n-3 PUFA treatment in dogs with healed myocardial infarction that were either susceptible (VF+, n = 31) or resistant (VF-, n = 31) to ventricular tachyarrhythmias induced by a 2 min coronary artery occlusion during the last minute of a submaximal exercise test. HR and HRV were evaluated at rest, during submaximal exercise and in response to acute myocardial ischemia at rest before and after either placebo (1 g/day, corn oil, VF+, n = 9; VF- n = 8) or n-3 PUFA (docosahexaenoic acid + eicosapentaenoic acid ethyl esters, 1-4g/day, VF+, n = 22; VF-, n = 23) treatment for 3 months. The n-3 PUFA treatment elicited similar increases in red blood cell membrane, right atrial, and left ventricular n-3 PUFA levels in both the VF+ and VF- dogs. The n-3 PUFA treatment also provoked similar reductions in baseline HR and increases in baseline HRV in both groups that resulted in parallel shifts in the response to either exercise or acute myocardial ischemia (that is, the change in these variables induced by physiological challenges was not altered after n-3 PUFA treatment). These data demonstrate that dietary n-3 PUFA decreased HR and increased HRV to a similar extent in animals known to be prone to or resistant to malignant cardiac tachyarrhythmias.